Germination and growth response of three wheat cultivars to NaCl salinity - Saddam Hussain, Abdul Khaliq, Amar Matloob, Muhammad Ashfaq Wahid; Irfan Afzal (Soil & Environment, 2013)
Salinity adversely affects germination and establishment of crop plants. Germination and early seedling growth response of wheat to NaCl salinity was assessed in a laboratory bioassay. Seeds of three different wheat cultivars (Sehar-2006, AARI-2011 and Millat-2011) were sown in Petri dishes and three salinity levels (6.8, 13.2 and 19.0 dS m-1) were imposed by developing NaCl solution concentration of 0.5, 1.0 and 1.5%, respectively. A control (distilled water) was maintained for each cultivar for comparison. Data regarding germination attributes and early seedling growth of wheat were recorded. Results revealed that increasing concentration of NaCl solution resulted in gradual reduction in seed germination and suppression of early seedling growth in all wheat cultivars. However, pronounced differences regarding salinity tolerance were observed among three wheat cultivars. Millat-2011 recorded least (11-40%) suppression in final germination percentage at different salinity levels as compared to 10-86% and 19-72% reduction observed for AARI-2011 and Sehar-2006, respectively. Millat-2011 also suffered less reduction in seedling dry biomass (21-43%) than 29-97% and 14-86% recorded for AARI-2011 and Sehar-2006, respectively. Millat-2011 appeared superior to Sehar-2006 and AARI-2011 due to its better germination and early seedling growth even at high salinity levels. Millat-2011 may tolerate moderate levels of salinity and may be tried for its field appraisal for cultivation on marginal salt affected lands.`